Rereview Literature: Effect of Forensic Audit, Anti-Fraud, External Audit, Individual Morality, and Fraud Knowledgeagainst Fraud Prevention - Agustina R.T Sitompul; Debora Anjany Situmorang; Ibbie Falia; Handriyani Dwilita (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This Research Aims To Examine The Influence of Forensic Audit, Anti-Fraud Awareness, External Audit, Individual Morality, And Fraud Knowledge On Fraud Prevention In Organizations. Fraud is a common problem That Often Occurs in Companies Financially and Financially. Using A Literature Review Approach, This Research Compiles And Examines Various Previous Studies Related to Understanding The Relationship Between These Factors. The Results of the Study Show That Forensic Audits Are A Determining Factor in Detecting and Preventing Conditions by Strengthening Supervision and Transparency. Understanding Anti-Fraud Among Employees Is Proven To Strengthen Compliance With Existing Procedures And Provisions. Additionally, External Audits Provide Independent Assessments That Can Reduce Financial Risks. Individual Morality Contributes to the Selection of Ethical Decisions, While Knowledge of Fraud Strengthens The Ability of Individuals and Organizations to Recognize and Prevent Acts From Occurring. These Fings Call for Integrating All of these Factors Into Fraud Prevention Strategies to Create a Safer and More Accountable Environment. It is hoped that this Research Will Provide Insight for Practitioners and Scientists in Designing Effective Policies to Prevent Fraud in Various Sectors.